Twitch, Fish, Pokémon and Plumbers: Game live streaming by nonhuman actors. (April 2022) - Johnson, Mark R.; Jackson, Nathan J.
In this exploratory paper, we consider the phenomenon of gameplay live streaming by nonhumans. The live streaming of games, exemplified by the platform Twitch.tv, has emerged in recent years as a major and growing component of gaming culture. Although previous research has addressed some agential dimensions of streaming, scholarship has yet to examine the unusual phenomenon of watching streams lacking any kind of human agent. Ordinarily a human streamer operates gameplay and directs the flow of conversation, curating the content of the stream and mediating the agency of other participants. Removing the central figure of the human streamer thus creates what we call an 'agency gap' to be filled by other users. In this article, we explore different ways this occurs through four case studies involving the broadcast of gameplay by biological and digital nonhumans. These range from random number generators and automated controller inputs, to a live fish with a motion tracker observing its movements around its tank (with these movements then being used to attempt completion of a digital game). Through these case studies, we argue that the absence of a human streamer democratises video game play through ways of experiencing games which were not possible until the emergence of game live streaming. To this end we interrogate when and how nonhuman streamers can also be influenced by the agency of human spectators, and how the stakes of these streams are understood in relation to the game being played and spectator motivation. We further characteristic the distinction between human and nonhuman agencies in terms of affective intentionality. Game streaming allows for an unprecedented visibility of nonhuman play which merits close attention; this paper consequently problematises current understandings of nonhuman play in an era of gameplay streaming, and extends and challenges scholarship in both of these areas.